2008
DOI: 10.1089/hyb.2008.0007
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Definition of a Chimpanzee and Human Conserved CD6 Domain 1 Epitope Recognized by T1 Monoclonal Antibody

Abstract: Scavenger receptor cysteine-rich (SRCR) domains are evolutionally conserved modules that display complex structures stabilized by key amino acids, while some other residues have evolved with a relative independence, thus allowing the functional diversity of these receptors. CD6, a highly glycosylated membrane protein predominantly expressed on lymphocytes, contains three SRCR domains. The lack of CD6 domain crystal structure has limited the characterization of the binding sites for the interacting molecules. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…It has been previously shown that the CD6 ligand, ALCAM, is induced on CD4 + T cells after activation, and blocking this interaction with inhibitory anti-CD6 mAb inhibits sustained entry into cell cycle (12,(25)(26)(27)(28)(29)(30). Thus, we activated highly purified CD4 + T cells from donors with the rs17824933 CC , rs17824933 CG , or rs17824933…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously shown that the CD6 ligand, ALCAM, is induced on CD4 + T cells after activation, and blocking this interaction with inhibitory anti-CD6 mAb inhibits sustained entry into cell cycle (12,(25)(26)(27)(28)(29)(30). Thus, we activated highly purified CD4 + T cells from donors with the rs17824933 CC , rs17824933 CG , or rs17824933…”
Section: Resultsmentioning
confidence: 99%
“…Although a full pharmacokinetic study was not performed, circulating itolizumab was detected by ELISA using as antigen CD6 SRCR1, the domain recognized by this antibody. 26 Results are shown in Figure S2. In spite of the higher dose administered during the maintenance phase in group A, the amount of itolizumab in sera from most of the patients appeared to be roughly the same at AI and AM weeks, with only slightly increased values at the latter point, at least as determined by the absorbance measurements.…”
Section: Itolizumab Administration Did Not Induce a Measurable Anti-imentioning
confidence: 99%
“…26 Itolizumab did not inhibit soluble ALCAM binding to CD6-expressing HEK293 cells 26 and did not cause T cell depletion in rheumatoid arthritistreated patients. 27 In experiments in vitro with peripheral blood mononuclear cells (PBMC) from healthy donors, itolizumab inhibited proliferation in the presence of soluble ALCAM and IL-2; downregulated the phosphorylation of intracellular proteins involved in the CD6-mediated activation pathway; and reduced IFN-γ, IL-6 and TNF production.…”
Section: Introductionmentioning
confidence: 98%
“…This antibody recognizes the membrane-distal domain 1 of CD6 and was not able to inhibit soluble ALCAM binding to CD6-expressing HEK-293 cells. 32 Moreover, itolizumab did not cause T cell depletion when used as monotherapy in RA patients. 33 In experiments in vitro with peripheral blood mononuclear cells (PBMC) from healthy donors, itolizumab reduced IFN-g, IL-6 and TNF production.…”
Section: Introductionmentioning
confidence: 97%